Characteristics Of Pediatric Tuberculosis Patients Hospitalized At dr. Soebandi Public Hospital Jember - Muhammad Ali Shodikin; Desie Dwi Wisudanti; Annisa Nadhifa Witanto (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Background: Tuberculosis (TB) remains a major public health problem globally. TB in children is an important component in TB control. The diagnosis of TB in children until now is still challenging, underdiagnosis often occurs in primary health facilities in Indonesia. This study aims to describe the demographic and clinical features of pediatric tuberculosis patients hospitalized in a tertiary care center.Methods: This study reviewed medical records of children with TB who were hospitalized in a referral hospital in Jember, East Java, Indonesia from January 2018 through December 2019.Results: Among 96 patients, 33,3% happened in the age group of 15-18 years, 53.1% were females, 35,4% had severely underweight nutritional status, majority (84,4%) live in rural area, 79,2% without known TB contact history and 81.1% were new cases. Pulmonary TB was the most common diagnosis (80,2%). Only 4.1% had co-infection with Human Immunodeficiency Virus (HIV) and 4.2% were reported to be resistant to anti-TB drugs. The most common symptoms were fever (84.3%), cough (65.6%), and dyspnea (65.6%). The miliary lesion was the most common lesions on chest X-ray examination results. The successful therapy reached a percentage of 61.4% of all cases.Conclusions: The majority of pediatric TB patients were diagnosed clinically and chest X ray. Examination of HIV status and drug-sensitivity testing is low. The rate of successful therapy was still under WHO target.. Keywords: tuberculosis, children, characteristics